EVALUATION OF THE PROVISION OF SEWERAGE SERVICES AMONG THE RESIDENTS OF KENOL TOWN, MURANG’A COUNTY, KENYA - NG’ANG’A, RUFUS KINYANJUI; Kagendo, Jane; Obiero, Kennedy (IJRDO - Journal of Social Science and Humanities Research, 2020)
Globally about 2.6 billion people do not have efficient sanitation services. Most of these challenges are found in third world countries that lack sufficient and adequate drainage and solid waste management strategies. Most countries in the sub-Saharan Africa have settlements that are inadequately supplied with sewage services. Kenol town in Murang’a County emerged as a market Centre in the 1990s and a petrol station. It subsequently grew into an urban settlement with little or no prior planning. The town grew rapidly as a sub County head quarter leading to sharp increase in population that needed among other social amenities housing. This has created a challenge on provision of sewerage services in the town. The study aimed at evaluating the provision of sewerage services among the residents of Kenol town, Murang’a County, Kenya. The study adopted a descriptive study design, the target population was 778 individuals. Both qualitative and quantitative data were collected from 264 respondents using interview guides and questionnaires. Collected data were analyzed using SPSS Version 21. Descriptive and linear regression statistics were used analyse the data and help to establish existing relationships between the independent variables and the dependent variable. The study established that there were numerous factors could be implied for poor provision of sewerage services to residents of Kenol town. Unplanned settlements was found to have a significant relationship (coefficient= -2.701, df=1, p= 0.036) with poor provision of the sewerage services. Thus, the study recommends that the County Government should ensure that all buildings and any other form of settlement are planned prior to construction to enable easy provision of the services. The County Government should formulate a policy which puts strict and punitive measures to any individual who does not adhere to physical planning and sewerage designs while setting up any structure. These findings may improve the status of other urban centres that are coming up and ease provision of sewerage services.